2021
DOI: 10.1111/and.13985
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of dexmedetomidine on ischaemia‐reperfusion injury in an experimental rat model of priapism

Abstract: The study aimed to investigate the effects of dexmedetomidine against ischaemia‐reperfusion injury occurring after priapism in a model of induced‐priapism in rats. A total of 18 male rats were randomised into three groups. Group 1 was the control group. A priapism model was performed rats in Group 2 and then ischaemia‐reperfusion injury was evaluated. Group 3 had similar procedures to the rats in Group 2. Rats in Group 3 additionally had 100 μg/kg dexmedetomidine administered intraperitoneally immediately afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…A number of cytokines involved in the etiopathogenesis of COVID-19 have a well-known role in both inflammation and thrombosis: IL-6 in particular is linked to multiple such procoagulant pathways, purportedly through tissue factor expression on mononuclear cells [ 4 ]. Furthermore, available data heavily stresses IL-6's crucial role in COVID-19 pathophysiology [ 5 ] as well as in murine models investigating ischemic priapism [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of cytokines involved in the etiopathogenesis of COVID-19 have a well-known role in both inflammation and thrombosis: IL-6 in particular is linked to multiple such procoagulant pathways, purportedly through tissue factor expression on mononuclear cells [ 4 ]. Furthermore, available data heavily stresses IL-6's crucial role in COVID-19 pathophysiology [ 5 ] as well as in murine models investigating ischemic priapism [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…DEX has been proven to prevent acute kidney and lung injury by inhibiting mitochondrial damage, cellular inflammation, and apoptosis [Qiu et al, 2018;Tan et al, 2018]. Kölükçü et al, 2021 revealed that DEX has a protective effect against I/R injury in penile tissue, increasing antioxidants while reducing pro-inflammatory cytokine levels. Tuglu et al [2015] reported that DEX exhibited a dosedependent antioxidant-protective effect in testicular I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, α2AR agonists can inhibit the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) (JAK/STAT) pathways [Schneider et al, 2016;Nguyen et al, 2017;Meng et al, 2018;Lankadeva et al, 2021]. DEX exhibits a protective effect against I/R injury through oxidative damage and by inducing antiapoptotic activity [Kölükçü et al, 2021]. Additionally, it exhibits anti-inflammatory and antiapoptotic effects by inhibiting both the NF-κB signaling pathway and caspase-3-related apoptosis [Sun et al, 2018].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anesthetic drugs have discrepant effects on patients' immune milieu, desflurane alone or with NO 2 cause significant increase in systemic interleukin (IL)-6 one day after surgery [7]. On contrary, sevoflurane can attenuate the inflammatory response during cardiopulmonary bypass [8] and dexmedetomidine, in ischemia-perfusion animal model, decreased levels of IL-1β, IL-6 and tumor necrosis factor-α (TNF-α) [9].…”
Section: Introductionmentioning
confidence: 99%